Dual tolerance of ageratum (Ageratum conyzoides L.) to combined pollution of acid and cadmium: Field survey and pot experiment. (15th January 2023) - Wang, Zhongzhen; Wang, Hongbin; Wang, Haijuan; Qin, Yongrong; Cui, Suping; Wang, Guanghui
Abstract: A field survey and pot experiment were carried out to screen tolerant plants growing in cadmium (Cd)-polluted mining areas which were co-polluted with acid in soil, and the related physiological and biochemical mechanisms were also analyzed. Thirty-seven species of wild plants and their corresponding soil were collected from a farmland around the mining areas. Ageratum ( Ageratum conyzoides L.) with strong Cd-accumulative ability was selected, and its tolerance experiment for acid and Cd with different levels were carried out separately or orthogonally, respectively. Furthermore, the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT), and the contents of malondialdehyde (MDA), photosynthetic pigments, soluble sugar and proline in its leaves were determined. The results showed that the Cd accumulation in ageratum and sticktight ( Bidens pilosa L.) was relatively high, but the latter has been well documented, so we focused on ageratum in the present work. In pot experiment, ageratum grew normally at 100 mg kg −1 Cd in soil, and the Cd concentrations in its roots, stems and leaves were 75.37 ± 7.37, 31.01 ± 3.76 and 53.92 ± 10.05 mg kg −1, respectively. In the case of acid tolerance experiment, all plant individuals of ageratum grew normally when soil pH was over 3.5. In the orthogonal experiment, the Cd accumulation in this plant increased with the decrease of soil pH under the same Cd treatment. Under strong acid conditions, the activity of SOD in leaves of ageratum was increased significantly. When the Cd concentration was 10 mg kg −1 and the soil pH was 5.5 or 3.5, the activities of POD and CAT were significantly increased. In addition, based on stepwise regression analysis, the leaf Cd concentration was significantly positive correlated with the activities of SOD and POD in leaves of ageratum. Therefore, ageratum not only had a strong tolerance for Cd and acid pollution in soil, but also had a strong ability to accumulate Cd. As a common plant in the mining area, it has a great potential for the phytoremediation of Cd and acid co-contaminated soil. Highlights: A good plant candidate was found for soil environmental management of Cd and acid co-pollution. About 54 mg kg −1 leaf Cd in ageratum was recorded when treated with 100 mg kg −1 Cd. Ageratum grew healthily when soil pH was over 3.5. The activities of SOD and POD had a significant positive correlation with leaf Cd concentration. Ageratum had a potential for phytomediation of Cd and acid co-polluted soil with 3130 US$ hm −2 .